基于EDEM的组合清理筛筛分仿真和性能分析Screening simulation and performance analysis of the combined cleaning screen based on EDEM - 张昊晨，张超，曹宪周，刘海芃，高涛 ZHANG Haochen，ZHANG Chao，CAO Xianzhou， LIU Haipeng，GAO Tao (Zhongguo youzhi, 2023)
为优化平面回转筛的结构和工艺参数，提高组合清理筛的筛分处理量和筛分效率，采用离散元软件EDEM对组合清理筛的平面回转筛分过程进行模拟仿真，探究颗粒在筛分过程中的运动规律，并仿真分析了回转半径、回转速度和筛面倾角对组合清理筛筛分处理量和筛分效率的影响。结果表明，提高回转半径、回转速度和筛面倾角均可提高组合清理筛筛分处理量，但会降低筛分效率（物料提取率和除杂率）。在回转速度为420 r/min左右、回转半径为20 mm左右、筛面倾角为7°~ 9°时，组合清理筛的筛分效率较好，筛分处理量也较大。In order to optimize the structure and process parameters of the rotary sieve classifier and improve the screening capacity and screening efficiency of the combined cleaning screen, the discrete element software EDEM was used to simulate the rotary screening process of the combined cleaning screen. The movement pattern of particles in the screening process was explored, and the effects of the radius of rotation, the rotation speed and the inclination angle of the screen surface on the screening capacity and screening efficiency of the combined cleaning screen were simulately analyzed. The results showed that increasing the radius of rotation, rotation speed and inclination angle of the screen surface could increase the screening capacity of the combined cleaning screen, but reduced the screening efficiency (material extraction rate and impurity removal rate). When the rotary speed was about 420 r/min, the radius of rotation was about 20 mm, and the inclination angle of the screen surface was 7°-9°, the screening efficiency of the combined cleaning screen was better, and the screening capacity was also larger.